HBR guide to office politics - Dillon, Karen (Editor) (Harvard business review guides, 2015)
The problem is, you can't just keep your dead down. You need to work productively with your colleagues even the challenging ones-for the good of your organization and your career. How can you do that without crossing over to the dark side? By acknowledging that power dynamics and unwritten rules exit-and by constructively navigating them. :Politics" needn't be a dirty word. You can succed at work without being a power grabber or a corporate climber, and the expert advice in this guide will help. You will get better at: - Building relationships with difficult people. - Gaining allies and influencing others. - Working through tough - but productive - conversations.- Wranging the resources you need. - Moving up without ruffling feathers. - Dealing with the boss's pet. - Copong with office bullies and cliques. - Claiming credit when it's due. - Avoiding power games and petty rivalries. - Collaborating with competitive peers.